Implementation of Student Data Applications at Tinta Emas Vocational High School - Rudi Prasetya; Danang Sutrisno; Hardian Mursito (Institut Teknologi Nasional, Bandung, 2021)
Every organization expects convenience, speed, efficiency and accuracy in their activities, but the level of mastery a technology in each person varies, it becomes a factor in the difficulty of implementing a technology directly. SMK Tinta Emas, is an educational organization that has a vision to improve services in the school service information system to make easier student registration process. This system will accelerate the work process and achieve work effectiveness. The problem that occurs at SMK Tinta Emas is how to implement the application for staffs and teachers with various information technology knowledge backgrounds therefore in the application later there will not be many obstacles that occur due to errors in the use of student data. The community service team as an intermediary between the makers of the student data system involved in the system was asked to provide direction in socialization and education. Finally, the community service team hopes that this implementation and socialization will produce good results for the smooth process of modernizing school student data by applying information technology.